2016
DOI: 10.1016/j.jcat.2015.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights for enhancing activity and stability of Nb-incorporated silicates for selective ethylene epoxidation

Abstract: Significant ethylene epoxidation activity was observed over niobium (Nb) incorporated mesoporous silicate materials Nb-KIT-5, Nb-MCM-48, and Nb-TUD-1, with hydrogen peroxide (H 2 O 2) as oxidant and methanol (MeOH) as solvent under mild operating conditions (35 °C and 50 bars). No CO 2 as byproduct was detected at these conditions. The measured ethylene oxide (EO) productivity over Nb-TUD-1 materials (342-2539 g EO h-1 kg-1 Nb) spans a greater range than those observed with Nb-KIT-6 (234-794 g EO h-1 kg-1 Nb),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 36 publications
3
52
0
Order By: Relevance
“…The selectivity for EO is in the range of ~80% over W-KIT-6 and 46–73% with Nb-KIT-6. The observed EO yields are comparable with those reported for homogeneous Re-based (1610–4970 gEO/h/kg Re) [ 57 ] and conventional heterogeneous Ag-based catalysts (700–4400 gEO/h/kg Ag) [ 58 , 59 ]. However, H 2 O 2 decomposition (~80%) and metal leaching caused by Brønsted acid sites in these catalysts are major drawbacks [ 54 ].…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The selectivity for EO is in the range of ~80% over W-KIT-6 and 46–73% with Nb-KIT-6. The observed EO yields are comparable with those reported for homogeneous Re-based (1610–4970 gEO/h/kg Re) [ 57 ] and conventional heterogeneous Ag-based catalysts (700–4400 gEO/h/kg Ag) [ 58 , 59 ]. However, H 2 O 2 decomposition (~80%) and metal leaching caused by Brønsted acid sites in these catalysts are major drawbacks [ 54 ].…”
Section: Resultssupporting
confidence: 83%
“…Clearly, the challenge is to synthesize M-KIT-6 materials that are exclusively Lewis acidic by passivating the Brønsted acid sites. To address the stability of KIT-6, and to improve the utilization of H 2 O 2 , we studied Nb-TUD-1 as a catalyst and found that it showed superior activity (~2500 g EO/h/kg Nb) compared to other Nb- or W-based silicates [ 59 ]. The EO productivity was further improved to ~4000 g EO/h/kg Nb by decreasing the Brønsted acid sites achieved by lowering the Nb loading.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct oxidation of ethylene to epoxyethane with molecular oxygen is a significant synthetic method for both industry and academia. During the last decades, many research works have been focused on epoxidation reactions of ethylene by supported catalysts such as transition metal complexes and metal nanoparticles [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%